TEACHING RUSSIAN LANGUAGE IN FOREIGN LANGUAGE GROUPS OF STUDENTS USING DIGITAL TECHNOLOGIES (American Journal of Pedagogical and Educational Research, 2024)
The article highlights the problems of using digital technologies that contribute to satisfying the development of linguistic, communicative and linguistic (cultural-linguistic) competencies of students.